Methodology of Operation Efficiency Prognosis - Bagdonas, V.; Daunoras, J.; Dervinienė, A. (Elektronika ir Elektrotechnika, 2006)
The methodology of operation efficiency estimations compilation and processing (according many rates) performed by group expert is discussed in this article. The methodology is based on search and use of experts’ competence rates, what can be get applying excess of the experts offered information. Such methods and algorithms are described in literature, but they are not universal and applicable just in that case, when importance of goals independent from goals consummation. Therefore, our improved methodology (without noted limitation) of processing group expert estimations is discussed in this paper. The methodology is based on application of Sugeno criterions and fuzzy integrals. Il. 2, bibl.6 (in English; summaries in English, Russian and Lithuanian).